Effect of Dopant on the Morphological and Electrical Properties of Polyaniline/MCM-41 Nanocomposites - Ameen, Sadia; Husain, M.; Shaheer Akhtar, M.; Soon Kim, Young; Shin, Hyung-Shik (Asian Journal of Chemistry, 2010)
The novel organic-inorganic nanocomposite was prepared with polyaniline (PANI) and mesoporous MCM-41 by the polymerization of aniline hydrochloride monomer. The structural, crystalline and Raman results confirmed the formation of the nanocomposites through the interaction between PANI molecules and MCM-41. DC conductivity of the nanocomposites was significantly affected by the incorporation of HCl doped PANI molecules into PANI/MCM- 41 nanocomposites. It was observed that the undoped polyaniline/MCM-41 nanocomposite presented an electrically insulating DC conductivity of the order of 10-13 ohm-1 cm-1 and after the introduction of HCl doped PANI molecules into MCM-41, the proton conductivity reached the order of 10-3 ohm-1 cm-1.